Short message service (SMS) reminders and real-time adherence monitoring improve antiretroviral therapy adherence in rural Uganda - Haberer, Jessica E.; Musiimenta, Angella; Atukunda, Esther Cathyln; Musinguzi, Nicholas; Wyatt, Monique A; Ware, Norma C; Bangsberg, David R (Wolters Kluwer Health, Inc., 2016)
Objective: To explore the effects of four types of short message service (SMS) plus real time adherence monitoring on antiretroviral therapy (ART) adherence: daily reminders, weekly reminders, reminders triggered after a late or missed dose (delivered to patients), and notifications triggered by sustained adherence lapses (delivered to patient-nominated social supporters). Design: Pilot randomized controlled trial. Methods: Sixty-three individuals initiating ART received a real-time adherence monitor and were randomized (1 : 1 : 1): (1) Scheduled SMS reminders (daily for 1 month, weekly for 2 months), then SMS reminders triggered by a late or missed dose (no monitoring signal within 2 h of expected dosing); SMS notifications to social supporters for sustained adherence lapses (no monitoring signal for >48 h) added after 3 months. (2) Triggered SMS reminders starting at enrolment; SMS notifications to social supporters added after 3 months. (3) Control: No SMS. HIV RNA was determined at 9 months. Percentage adherence and adherence lapses were compared by linear generalized estimating equations and Poisson regression, respectively. Results: Median age was 31 years, 65% were women, and median enrollment CD4þ cell count was 322 cells/ml 97% took once daily tenofovir/emtricitabine/efavirenz. Compared to control, adherence was 11.1% higher (P¼0.04) and more than 48-h lapses were less frequent (IRR 0.6, P¼0.02) in the scheduled SMS arm. Adherence and more than 48-h lapses were similar in the triggered SMS arm and control. No differences in HIV RNA were seen. Conclusion: Scheduled SMS reminders improved ART in the context of real-time monitoring. Larger studies are needed to determine the impact of triggered reminders and role of social supporters in improving adherence.
Adherence monitoring improve antiretroviral therapy adherence in rural Uganda.
Keywords: Antiretroviral therapy, real-time adherence monitoring, short message service (SMS)